Realizing Ideological Political Education in Political Parties Policy Recommendations for Provincial Regional People's Representative Assembly and Regional Governments - Hidayatullah Hidayatullah; Ayatullah Hadi; Firra Nurfajriah; Nisa Lestari; Nadila Putri (Visi Pencerah Nusantara, 2025)
This research aims to formulate policy recommendations for the Provincial DPRD and Local Government in realizing systematic, adaptive, and inclusive ideological political education within political parties. Using a qualitative approach with the Systematic Literature Review (SLR) method, this research analyzes scientific findings from reputable national and international journals published within the last six years (2020-2025), obtained through the Dimensions and Scopus databases. Selection criteria included thematic relevance, publication quality, full-text access, and use of Indonesian or English. The study results indicate that ideological polarization has become a significant structural challenge to strengthening political education within political parties, hindering the regeneration process and weakening commitment to democratic values. The findings also highlight the lack of a structured political education curriculum and the low digital literacy of young cadres. Therefore, synergy between DPRDs, local governments, and political parties is necessary to establish a democratic and sustainable political education ecosystem. This research recommends the need for evidence-based policies to design a cross-disciplinary ideological curriculum, as well as strengthening digital media literacy capacity in political education cadres at the regional level.